Application of genetic algorithms to model parameter identification of a recombinant e.coli high-cell density fed-batch fermentation / Kamaruddin Mamat and Farida Zuraina Mohd Yusof - Mamat, Kamaruddin; Mohd Yusof, Farida Zuraina (2008)
In this work, a genetic algorithm was used to estimate both yield and kinetic coefficients of an unstructured model representing a fed-batch high-cell density fermentation of Escherichia coli (E. coli). The model based on the General State Space Dynamical Model was used to represent the three major metabolic pathways: oxidative growth on glucose, fermentative growth on glucose and oxidative growth on acetate. The structure of the kinetic equations was derived from literature and adapted to represent experimental results. Genetic Algorithm was used to minimize the normalized quadratic differences between simulated and real values of side variables X. A and W by manipulating both yield and kinetic coefficients.